Chapter 2: MEDICAL INFORMATION COMMONS: CONCEPTUAL, LEGAL AND ETHICAL CONSIDERATIONS FOR STAKEHOLDERS - Geary, Janis (Edward Elgar Publishing, 2022)
The practice of medicine, the delivery of health care and public health services, and biomedical research have all become more data-intensive. The importance of managing information has become apparent, and with it attention to building knowledge commons. This chapter describes factors that influence the creation and use of diverse sets of data that enable biomedical advances. First, we characterize these resources as a Medical Information Commons (MIC). We describe commons scholarship generally and MICs more specifically, and describe approaches to commons governance. Next, we highlight specific issues around privacy and consent, and then discuss participant interests in the commons. We describe the negative history of marginalized and racialized populations, and finally we pull all of these concepts together and discuss challenges in building MICs that are trustworthy and inclusive, and meet the needs of marginalized and racialized populations.